1109 Total Body Hypothermia and Circulating Biomarkers of Liver Function. (October 2012) - Gardner, D; Sanka, S; Pawaletz, A; Muniraman, H; Jennings, C; Vayalakkad, A; Victor, S; Clarke, P; Turner, MA
Abstract : Background and Aims: Total body hypothermia (cooling) improves outcome in hypoxic-ischaemic encephalopathy (HIE). This study tested the hypothesis that cooling affects the liver by examining whether cooling during HIE was associated with differences in clinically relevant biomarkers of hepatic metabolism. Methods: Clinical records in 3 centres were searched for babies with HIE and umbilical artery pH at birth ≤ 7.0 born between 01/07/2006 and 30/06/2011. Each centre adopted routine cooling on a different date. The results of blood tests reflecting hepatic metabolism measured according to clinical practice within 7 days of birth were collected. ANOVA was used to assess the associations between extreme values of each analyte, HIE grade and the use of cooling and to calculate estimated marginal means for each condition. Results: 127 babies were identified including 31 with Grade 1 (42% cooled), 65 with Grade 2 (80% cooled) and 31 babies with Grade 3 (90% cooled). Grade of HIE was associated with maximum AST [HIE1: mean 180 (s.e. 120); HIE2: 367 (85); HIE3: 850, (123)], maximum prothrombin time [HIE1: 18 (3); HIE2: 22 (2); HIE3: 36 (4)] maximum bilirubin [HIE1: 117 (9); HIE2: 108 (8); HIE3 68 (15)] and minimum albumin [HIE1: 28.5 (0.9); HIE2: 23.6 (0.7); HIE3: 20.1 (1)] but not with maximum ALT or maximum APTT. Cooling was not associated with any variables. Discussion: Clinically graded HIE was associated with markers of liver function. Cooling did not modify these associations. Liver and brain may have different susceptibilities to hypoxic-ischaemia or different responses to cooling.